Процес взаємодії церкви та інститутів державної влади: історія та сучасність - Лазор, К. П.; Лазор, К. П.; Lazor, К. (My University, 2013)
The article is devoted to the actual problem of political theory and practice – the formation of an optimal model interactions church and governmental institutions. The features of certain historical stages of state-church interaction. The analysis this form of interaction.
Лазор К. П. Процес взаємодії церкви та інститутів державної влади: історія та сучасність / К. П. Лазор // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 317-323.
Keywords: інтеракція церкви та інститутів державної влади; історичні етапи державно-церковної взаємодії; форми державно-церковної взаємодії; интеракция церкви и институтов государственной власти; исторические этапы государственно-церковного взаимодействия; формы государственно-церковного взаимодействия; Interaction of the Church and government institutions; Historical stages of church-state cooperation; forms of state-church cooperation